Time pressure in surgical teams, a help or a hindrance to patient safety? - Annet van Harten; Theo J.H. Niessen; Jur J. Koksma; Hein G. Gooszen; Tineke A. Abma (Heliyon)
Background: Patient safety requires mindful routines in the operating room. Usually, time pressure is presented as an unavoidable constraint to mindful routines and a consequence of workload imposed on teams. We aim to understand time pressure and how it interacts with developing mindful routines. Methods: This naturalistic case study was conducted with a surgical team in a Dutch academic hospital using ethnographic methods including participant observation, interviews, and fieldnotes. The researcher observed the team for 103 h. Our analysis integrates habit theory and mindful organising principles. Results: Team culture reflected deference to speed, preoccupation with productivity, conflict avoidance, and value on affective relationships. Conflicting priorities arose from differences in safety norms, worries about time, and beliefs about what saves time. Addressing these conflicting priorities, however, was rare. Creating shared Situational Awareness (SA) helped prevent or mitigate time pressure, though it was not a consistently embedded routine. New routines were often compromised under time pressure, while established habits showed resilience to time constraints. Conclusions: Rather than being workload-driven, time pressure emerged as a co-constructed outcome of conflicting priorities and the preservation of affective relationships. The imperative to save time motivated shared situational awareness and the formation of new mindful routines. We recommend enhancing mindful routines by refining current practices in mortality and morbidity meetings, expanding stakeholder involvement, and addressing prevailing concerns.